2013
DOI: 10.1182/blood-2013-04-499335
|View full text |Cite
|
Sign up to set email alerts
|

Protein S levels and the risk of venous thrombosis: results from the MEGA case-control study

Abstract: Key Points• Low free protein S and low total protein S levels could not identify subjects at risk for venous thrombosis in a population-based study.• Protein S testing and subsequent testing on PROS1 mutations should not be considered in unselected patients with venous thrombosis.In thrombophilic families, protein S deficiency is clearly associated with venous thrombosis. We aimed to determine whether the same holds true in a population-based casecontrol study (n 5 5317). Subjects were regarded protein S defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 39 publications
(37 reference statements)
2
48
0
Order By: Relevance
“…Thus one would expect that blacks with MM, especially those treated with lenalidomide, will have a better outcome. 16 In fact, in a recent ECOG randomized trial that utilized lenalidomide in both arms, although response rates were similar, overall survival was significantly superior in non-whites (almost all blacks) compared with whites, supporting this hypothesis. 17 However, additional studies with information on trisomies and treatment will be important to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…Thus one would expect that blacks with MM, especially those treated with lenalidomide, will have a better outcome. 16 In fact, in a recent ECOG randomized trial that utilized lenalidomide in both arms, although response rates were similar, overall survival was significantly superior in non-whites (almost all blacks) compared with whites, supporting this hypothesis. 17 However, additional studies with information on trisomies and treatment will be important to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…29 34 Using this cut-off to dichotomise patients may not be sensible; some studies have shown a gradation of risk with levels, 35 whereas another study showed that, for example, protein S deficiency does not seem to be a risk factor for VTE unless levels are very low (<0.10th percentile free protein S). 29 When should heritable thrombophilias be looked for?…”
Section: How Are Heritable Thrombophilias Diagnosed?mentioning
confidence: 99%
“…While traditionally these were seen as the strongest risk factors for thrombosis, recently some doubt has been shed on that idea. 16,17 In this study, none of the patients had these genetic causative factors. Hence, these causes and risk factors need to be evaluated for prevention of DVT.…”
mentioning
confidence: 62%